Synthesis, characterization, and crystal structure of two zinc linear dicarboxylates. Issue 3 (September 2016) - Baca, Berenice Torruco; del Castillo, Luis Felipe; Vera-Cruz, Paula; Toscano, Rubén A.; Rodríguez-Hernández, Joelis; Balmaseda, Jorge
Abstract : Two different crystalline structures corresponding to a zinc adipate and a zinc succinate were determined combining: X-ray powder and single-crystal diffraction, infrared spectroscopy, thermal analysis, and true densities experiments. The zinc succinate crystal structure was determined by single-crystal X-ray diffraction. This compound crystallizes in the orthorhombic space-group Cccm with unit-cell parameters a = 4.792(1) Å, b = 21.204(6) Å, c = 6.691(2) Å, V = 679.8(3) Å 3, and Z = 8. Zinc adipate crystal structure was refined from the laboratory X-ray powder diffraction data by the Rietveld method. It crystallizes in the monoclinic space group P 2/ c with unit-cell parameters, a = 16.2037(17)Å, b = 4.7810(2)Å, c = 9.2692(6)Å, β = 90.329(3)°, V = 718.07(9) Å 3, and Z = 4. The thermal expansion of it was estimated in 5.40 × 10 −5 K −1 . This contribution is a step on the way to systematize the regularities in the coordination diversity between linear dicarboxylates and transition metal–inorganic buildings units of metal–organic frameworks.